KEMANDIRIAN KONSUMEN DI ERA GLOBALISASI DAN PERDAGANGAN BEBAS (Kajian Mengenai Undang-undang Perlindungan Konsumen No. 8 Tahun 1999 Terhadap Perlindungan Hak-hak Konsumen) - Emei Dwinanarhati Setiamandani (Universitas Widya Gama Malang, 2018)
The Application of a free trade in the globalization are has resulted in a tight competition in the economic sector. In order to protect consumers from detrimental actions done business actors in the transaction of products and services, the government have made a regulation on the consumer protection. This present study was intended to understand the protection guarantee the government give on the basis of the 1999 consumer protection laws in the free trade in this globalization era. In this present study, a normative judicial approach was employed. In this approach, a legal examination was made based on the study on the legislation regulation and literatures in order to analyse the emerging problems. The result of the study showed tha the application of the 1999 consumer protection laws no.8 proved that the protection to the consumers was given by all parties, namely among others, the government, the people, and consumer protection organizations. It hopefully may give the consumers in the globalization era an equal position with the business actors. Kata kunci: Globalisasi, perlindungan, konsumen, dan pemerintah